Exploring the link of real options theory with dynamic capabilities framework in open innovation-type merger and acquisition deals - Andrejs Čirjevskis (Journal of Risk and Financial Management, 2021)
Although it is well established that acquisition-based dynamic capabilities have important consequences for merger and acquisition (M&A) processes, direct evidence on how real option applications can measure a dynamic capability-based synergy in open innovation-type M&A deals has been scarce. This study draws from seminal research on real options theory to explore some of these benefits and limits to value a synergy in one recent highly strategic acquisition. To strengthen the identification of causal effects, the paper develops the proposition that justifies the role of dynamic capabilities as antecedents of the success of open innovation-type M&A deals in the ICT industry and demonstrates real options' application to measure M&A synergies. To test the internal and external validity of the proposition, the explorative case study on Samsung's acquisition of Harman International Industries was analyzed and interpreted. This study contributes important empirical evidence to bear on the literature on open innovation theory, dynamic capabilities framework, and real options theory.
Keywords: 330; acquisition; dynamic capabilities; open innovation; real option; synergy